Jihadism expansion in Kenya and its impact on Eastern Africa - Stempień, Marta (Przegla̜d religioznawczy, 2018)
Despite the many sources of tension in the history of Kenya, until recently, interreligious relationships, especially the Christian-Muslim relations, were seen as mostly harmonious. This situation has changed, and religious tensions are now one of the main problems of Kenyan government. Concerns that Islam spreads in Kenya rise. In addition, the jihadist structures gain popularity. Thinking about the main countries in which the jihadists create their structures, usually Kenya is not mentioned. However, the position of the African countries on the map of "international terrorism" may change in the near future. The strategy of Al-Qaeda this state remains from many years as a target of attacks on opponents and a place of operational activities. The potential of this country can also become a field of interest to the Islamic State, a rival of Al-Qaeda for hegemony over the global salafi-jihadist movement. Currently, the interest flows from the Kenyan jihadists, as evidenced by their attachment to the structures of the self-proclaimed caliphate in Libya. The author analyzes the historical context of the Kenyan terrorism at the national level, points to numerous examples of terrorist attacks, explaining why the state is an attractive target, and at the same time a suitable environment for jihadi terrorists.